The Comparison of the Nearest Neighbor and Modified Sollin Algorithms for Determining the Shortest Tour for BNI Bank Branches in Lampung Province - Maharani, Assyfa Dwipa; Putri, Desiana; Sapitri, Nonik Mega; Notiragayu; Ansori, Muslim (Magister Program of Mathematics, Universitas Lampung, 2025)
BNI is one of the government -owned banks in Indonesia. At certain times, BNI experiences a significant increase in the number of customers, which can lead to long queues. In such situations, customers generally consider visiting other BNI branches. To optimize time and cost, it is necessary to have information to determine the shortest tour between BNI locations in Lampung Province. The purpose of this study is to determine the shortest tour among 21 BNI locations in Lampung Province. The results show that both the Nearest Neighbor Heuristic Algorithm and the Modified Sollin’s Algorithm produce the same solution for Euclidean distance data and Haversine distance data. However, for time-based data, the Modified Sollin’s Algorithm performs better than the Nearest Neighbor Heuristic Algorithm.